Clinical accuracy of preoperative breast MRI for breast cancer. Issue 8 (13th April 2017) - Tseng, Jennifer; Kyrillos, Alexandra; Liederbach, Erik; Spear, Georgia G.; Ecanow, Jacob; Wang, Chi‐Hsiung; Czechura, Tom; Kantor, Olga; Miller, Megan; Winchester, David J.; Pesce, Catherine E.; Rabbitt, Sarah; et al.
Abstract : Background: It is unclear if breast magnetic resonance imaging (MRI) is more accurate than mammography (MGM) and ultrasound (U/S) in aggregate for patients with invasive cancer. Methods: We compared concordance of combined tumor size and tumor foci between MRI and MGM and U/S combined to pathological tumor size and foci as the gold standard from 2009 to 2015. Tumor size was nonconcordant if it differed from the pathologic size by ≥33% and tumor foci was nonconcordant if >1 foci were seen. If one or both of the MGM or U/S was nonconcordant and the MRI was concordant, MRI provided greater accuracy. Results: Of 471 patients with MGM, US, and MRI, MRI was more accurate for 32.9% of patients for tumor size and for 21.9% for tumor foci. Patients for whom MRI had greater accuracy were compared to those who did not for clinical and tumor factors. The only significant factor was calcifications on mammography. Tumor size, stage, molecular subtype, histology, grade, patient BMI, age, mammographic density, and use of hormone replacement therapy were not significantly different. Conclusions: Breast MRI provides greater accuracy for a third of patients undergoing preoperative MGM and U/S. Mammographic calcifications were associated with MRI clinical accuracy for patients with invasive cancer.